Gender-Inclusive Governance for Environmental Sustainability in Smallholder Coffee Systems: Evidence from the Gayo Highlands, Indonesia - Vellayati Hajad; Ikhsan Ikhsan; Hajar Ashwad; Herizal Herizal (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
Smallholder coffee systems require effective governance to balance rural livelihoods and environmental sustainability. This study examines how gender exclusion shapes governance effectiveness and sustainability outcomes in the Gayo Highlands, Indonesia. Using qualitative interviews and policy analysis, it explores how institutional arrangements influence land management, climate resilience, and value chain dynamics. The findings reveal that fragmented regulations, weak coordination, and limited participation of women in land ownership, cooperative leadership, and decision-making processes undermine governance effectiveness and agroecosystem resilience. These conditions encourage short-term land-use strategies, reduce investment in soil conservation and agroforestry, and increase vulnerability to climate change. Women’s participation remains largely symbolic, limiting the integration of local ecological knowledge into governance processes. The study concludes that gender exclusion constitutes a key structural barrier to sustainable coffee systems. Improving sustainability therefore requires strengthening institutional coordination, expanding women’s access to resources and leadership, and embedding gender-responsive mechanisms within governance structures. It further recommends adopting gender-inclusive polycentric governance to enhance accountability, support adaptive decision-making, and improve environmental outcomes in smallholder coffee systems.